2020
DOI: 10.3390/ijerph17072398
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Wall: Death Education at Middle School as Suicide Prevention

Abstract: This study investigates the psychological effects of participation in Death Education (DeEd) by middle school children in two towns in northeast Italy in which suicides occur to a greater extent than in the rest of the region. The aims of the project “Beyond the Wall” were inherent to the prevention of suicide, address existential issues and enhance the meaning of life through positive intentions for the future and reflection on mortality. It involved eight classes (150 students in four classes in the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 51 publications
(50 reference statements)
1
30
0
2
Order By: Relevance
“…They considered these encounters to be very meaningful experiences. The professionals working in this specific healthcare field are able to provide a unique point of view on the topic of death, but they were not regarded as omniscient or omnipotent, rather, the teachers and students perceived them as ordinary human beings, thus dispelling the aura of mystery and terror linked to death-related themes [ 40 , 63 , 64 , 65 , 66 , 67 ]. However, based on TMT and their DTA hypothesis, it is also possible that the language and coping skills learned through this program might serve to strengthen the aura of mystery surrounding death.…”
Section: Discussionmentioning
confidence: 99%
“…They considered these encounters to be very meaningful experiences. The professionals working in this specific healthcare field are able to provide a unique point of view on the topic of death, but they were not regarded as omniscient or omnipotent, rather, the teachers and students perceived them as ordinary human beings, thus dispelling the aura of mystery and terror linked to death-related themes [ 40 , 63 , 64 , 65 , 66 , 67 ]. However, based on TMT and their DTA hypothesis, it is also possible that the language and coping skills learned through this program might serve to strengthen the aura of mystery surrounding death.…”
Section: Discussionmentioning
confidence: 99%
“…DeEd can be achieved at different levels of prevention: primary, secondary and tertiary [ 11 , 13 , 17 , 18 ]. DeEd as primary prevention, on which the study reported in this article is focused, is implemented in situations where there is no recent experience of death but the topic is addressed in a preventive way, focusing on sharing one’s emotional experiences and building an appropriate and shared language [ 19 , 20 ]. Experiences of DeEd as primary prevention have shown that it does not produce negative effects but allows better management of related anxiety, decreases alexithymia, increases empathic understanding of others and approaches them by learning to understand their viewpoints and emotional experiences and to re-evaluate aspects of one’s life [ 13 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…DeEd as primary prevention, on which the study reported in this article is focused, is implemented in situations where there is no recent experience of death but the topic is addressed in a preventive way, focusing on sharing one’s emotional experiences and building an appropriate and shared language [ 19 , 20 ]. Experiences of DeEd as primary prevention have shown that it does not produce negative effects but allows better management of related anxiety, decreases alexithymia, increases empathic understanding of others and approaches them by learning to understand their viewpoints and emotional experiences and to re-evaluate aspects of one’s life [ 13 , 19 , 20 , 21 ]. Starting from different multidisciplinary contexts, DeEd can be carried out through moments of “formal” theoretical lessons, combined with “informal” lessons that may include imaginative techniques and art therapy experiences such as photovoice, phototherapy, and psychodrama [ 13 , 18 , 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a qualitative study of community death education in which participants were offered a death education course and were later asked to imagine they were affected by Amyotrophic Lateral Sclerosis (ALS) and had to prepare their Advanced Treatment Directives (ATDs) highlighted how reflecting upon the themes of the knowledge of having to die, palliative care and ATDs significantly helped participants to think to their death in a less distressful way and to be able to plan their future healthcare treatments and fundamental desires with less anxiety (14). Death education has moreover been demonstrated to be useful also to help prevent other significant public health concerns, such as for example the issue of suicide risk, especially among adolescents (15) and the likeliness of smoking (16).…”
Section: Introductionmentioning
confidence: 99%